ANALISIS BIAYA INDUSTRI KECIL PENGOLAHAN KAYU DAN PERABOT DI PANGKALAN KERINCI KABUPATEN PELALAWAN (STUDI KASUS UD. AUZAR BERSAUDARA DAN UD. DIRGANTARA) - Mazni, Mazni; Sadjati, Emy; Insusanty, Eny (Fakultas Kehutanan Universitas Lancang Kuning, 2017)
Wood processing and furniture industries are industries that convert wood into processed wood in the form of items such as tables, chairs, cabinets and others. UD. Auzar Bersaudara and UD. Dirgantara is an industry engaged in wood processing and furniture. UD wood furniture manufacturing and processing capacity. UD Auzar Bersaudara 667 units / year, with selling price / unit about Rp 135,000 - Rp 1,100,000. The results show that the total net profit of UD wood processing and furniture industries. Auzar Bersaudara Rp 178.359.699 / year. The value of BCR of wood processing and furniture industry UD. Auzar Bersaudara is 1.48, then the business is feasible. So it can expand its business further by enlarging the business in other ways. UD wood furniture manufacturing and processing capacity. Capacity UD Dirgantara about 659 units, with selling price / unit about Rp 200,000- Rp 450,000. The results show that the total net profit of UD wood processing and furniture industries. UD Dirgantara for 1 year amounting to Rp 159,531,733 / year. The value of BCR of wood processing and furniture industry UD. Dirgantara is 1.36, then the business is feasible to be implemented. So it can expand its business further by enlarging the business in other ways.